Diagnostic value of 18F-FDG PET in the assessment of myocardial viability in coronary artery disease: A comparative study with 99mTc SPECT and echocardiography - Al Moudi, M.; Sun, Zhonghua (Chinese P L A General Hospital * Institute of Geriatric Cardiology, 2014)
Objectives: To investigate the diagnostic value of 18F-FDG PET in the assessment of myocardial viability in patients with known coronary artery disease (CAD) when compared to 99mTc SPECT and echocardiography, with invasive coronary angiography as the gold standard.Methods: Thirty patients with diagnosed CAD met the selection criteria, with 10 of them (9 men; mean age 59.5 ± 10.5 years) undergoing all of these imaging procedures consisting of SPECT and PET, echocardiography and invasive angiography. Diagnostic sensitivity of these less invasive modalities for detection of myocardial viability was compared to invasive coronary angiography. Inter- and intra-observer agreement was assessed for diagnostic performance of SPECT and PET.Results: Of all patients with proven CAD, 50% had triple vessel disease. Diagnostic sensitivity of SPECT, PET and echocardiography was 90%, 100% and 80% at patient-based assessment, respectively. Excellent agreement was achieved between inter-observer and intra-observer agreement of the diagnostic value of SPECT and PET in myocardial viability (k=0.9).Conclusions: 18F-FDG PET has high diagnostic value in the assessment of myocardial viability in patients with known CAD when compared to SPECT and echocardiography. Further studies based on a large cohort with incorporation of 18F-FDG PET into patient management are warranted.